Filets Enseñanza de la física con material interactivo - ESQUEMBRE, Francisco; MARTIN, Ernesto; CHRISTIAN, Wolfgang; BELLONI, Mario (PEARSON EDUCACION-PRENTICE-HALL, 2004)
CONTIENE UN CD-ROM DEL LIBRO